Domestic Final Demand as a Determinant of R&D Activity in Selected Central and Eastern European Countries - Świeczewska, Iwona (Comparative Economic Research. Central and Eastern Europe, 2014)
This article presents the results of an empirical study conducted based on selected countries in Central and Eastern Europe. The study focused on the impact of domestic final demand for products manufactured by individual industries on the R&D activity in the country. The main research tools are the Leontief model and R&D multipliers. The application of the input-output methods allows domestic R&D expenditures to be broken down into institutional sectors to establish what part of the expenditures is embodied in products manufactured to meet final household demand, in exports, etc.